2015
DOI: 10.1021/ci500672v
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Screen Discovers Novel, Fragment-Sized Inhibitors ofMycobacterium tuberculosisInhA

Abstract: Isoniazid (INH) is usually administered to treat latent Mycobacterium tuberculosis (Mtb) infections, and is used in combination therapy to treat active tuberculosis disease (TB). Unfortunately, resistance to this drug is hampering its clinical effectiveness. INH is a prodrug that must be activated by Mtb catalase peroxidase (KatG) before it can inhibit InhA (Mtb enoyl-acyl-carrier-protein reductase). Isoniazid-resistant cases of TB found in clinical settings usually involve mutations in or deletion of katG, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 128 publications
(299 reference statements)
0
34
0
Order By: Relevance
“…[50] These PCA studies were performed using established protocols. [73,74] Briefly, eight different interpretable molecular descriptors were calculated and utilized to characterize the chemical properties of each compound: ALogP, molecular weight, number of rings, number of aromatic rings, number of rotatable bonds, number of hydrogen bond donors, number of hydrogen bond acceptors, and molecular fractional polar surface area. Pipeline Pilot then combined these eight descriptors in different ways, with different weights on each term, to reduce the dimensionality of the data into three Principal Components that describe most of the variance in the compounds.…”
Section: Methodsmentioning
confidence: 99%
“…[50] These PCA studies were performed using established protocols. [73,74] Briefly, eight different interpretable molecular descriptors were calculated and utilized to characterize the chemical properties of each compound: ALogP, molecular weight, number of rings, number of aromatic rings, number of rotatable bonds, number of hydrogen bond donors, number of hydrogen bond acceptors, and molecular fractional polar surface area. Pipeline Pilot then combined these eight descriptors in different ways, with different weights on each term, to reduce the dimensionality of the data into three Principal Components that describe most of the variance in the compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Results of several similar studies on proteins and their substrates were reported in the following years 911 . We have also used the Autodock suite as a tool for drug design and virtual screening against a number of targets, including HIV protease 1214 , tuberculosis targets 15,16 , and beta-secretase 17,18 . AutoLigand was used to identify druggable sites for stabilizing a protein-protein interface 19 and covalent docking was used to explore covalent inhibitors of protein tyrosine phosphatases 20 .…”
Section: Applications Of the Protocolmentioning
confidence: 99%
“…Automated docking of small molecules is applied in many drug design efforts, and due to the ubiquitous availability of large computational resources, high throughput virtual screenings are now routinely applied in campaigns to assess druggability of novel targets where often no binders are known. A large number of successful applications have been reported using a variety of docking techniques [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, despite the improvements in recent years, a number of issues remain unsolved.…”
Section: Introductionmentioning
confidence: 99%